Motivations of German Hospice Volunteers: How Do They Compare to Nonhospice Volunteers and US Hospice Volunteers?. (March 2016) - Stelzer, Eva-Maria; Lang, Frieder R.
We examined reasons of volunteering for hospice and nonhospice organizations in a study with 125 volunteers (22-93 years) from the United States and Germany. Motives of US and German hospice volunteers revealed similarities and few differences. Hospice volunteers are involved because they seek to help others, seek new learning experiences, seek social contacts, or seek personal growth. The US hospice volunteers reported motives related to altruistic concerns, enhancement, and social influence as more influential, while German hospice volunteers rated career expectations as being more important. Comparison of German hospice with nonhospice volunteers revealed stronger differences: German hospice volunteers scored higher on altruistic motives, while German nonhospice volunteers yielded higher scores on self-serving motives. Findings contribute to improved understanding of volunteering motivation and of activating or retaining hospice volunteers.